2019
DOI: 10.2147/ijn.s195892
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ocular anti-inflammatory activity of prednisolone acetate loaded chitosan-deoxycholate self-assembled nanoparticles</p>

Abstract: Background and purpose: Conventional topical ophthalmic aqueous solutions and suspensions are often associated with low bioavailability and high administration frequency, pulsatile dose and poor exposure to certain ocular parts. The aim of this study was to develop an ophthalmic nanoparticles loaded gel, for delivering prednisolone acetate (PA), to increase dosing accuracy, bioavailability, and accordingly, efficiency of PA in treating inflammatory ocular diseases. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The high drug loading capacity is of prime importance for clinical applications to maximize the drug/excipients ratio and minimize the hazards associated with the use of unnecessary chemicals. Although data in Table 1 shows that the size of PEG2- b -PLA1 micelles (146.90 ± 4.29 nm) is larger than that of PEG2- b -PCL10 micelles (64.26 ± 0.55 nm), the former is still in the nanometer range and has the potential to enhance drug efficacy (Hanafy et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high drug loading capacity is of prime importance for clinical applications to maximize the drug/excipients ratio and minimize the hazards associated with the use of unnecessary chemicals. Although data in Table 1 shows that the size of PEG2- b -PLA1 micelles (146.90 ± 4.29 nm) is larger than that of PEG2- b -PCL10 micelles (64.26 ± 0.55 nm), the former is still in the nanometer range and has the potential to enhance drug efficacy (Hanafy et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have used a different crosslinking agent, instead of TPP, such as sodium deoxycholate. For example, Hanafy et al [ 43 ] used a CH/PVA system crosslinked with sodium deoxycholate to embed prednisolone for the treatment of ocular inflammation diseases. Results obtained on female guinea pigs showed that optimized NPs formulation achieved a twofold increase in the prednisolone release after 24 h when compared with the commercial micronized drug loaded gel.…”
Section: Polymeric Nanocarriers For Ocular Drug Deliverymentioning
confidence: 99%
“…A new ophthalmic nanoparticulate gel composed of chitosan (CS), sodium deoxycholate (SD), and prednisolone acetate (PA) was prepared by Hanafy et al with the particle size of 480 nm ± 28 and the PDI of 1.396. In simulated tears of pH 7.4, the release of PA was found to be 98.6% in 24 h. The results of the anti-inflammatory in vivo test of the gel with NPs on guinea pig eyes was significantly better than the effect of the gel loaded with micronized PA [ 124 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%